1997
DOI: 10.1073/pnas.94.11.5792
|View full text |Cite
|
Sign up to set email alerts
|

Resource competition as a mechanism for B cell homeostasis

Abstract: Cellular competition for survival signals offers a cogent and appealing mechanism for the maintenance of cellular homeostasis [Raff, M. C. (1992) Nature (London) 356, 397-400]. We present a theoretical and experimental investigation of the role of competition for resources in the regulation of peripheral B cell numbers. We use formal ecological competition theory, mathematical models of interspecific competition, and competitive repopulation experiments to show that B cells must compete to persist in the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 34 publications
(31 reference statements)
3
61
0
Order By: Relevance
“…Third, there is a fundamental difference between antigenicity (capacity to bind an Ab) and immunogenicity (capacity to elicit an Ab) (19,29), with the first being a simple biochemical reaction and the second being a complex biological process involving several cell types and competition among cells capable of binding or responding to a specific immunogen (42)(43)(44)(45)(46)(47). Such competition results in the immune system preferentially using memory cells in responding to the presentation of an immunogen immunoreactive with the memory B-cell receptors (33).…”
Section: Discussionmentioning
confidence: 99%
“…Third, there is a fundamental difference between antigenicity (capacity to bind an Ab) and immunogenicity (capacity to elicit an Ab) (19,29), with the first being a simple biochemical reaction and the second being a complex biological process involving several cell types and competition among cells capable of binding or responding to a specific immunogen (42)(43)(44)(45)(46)(47). Such competition results in the immune system preferentially using memory cells in responding to the presentation of an immunogen immunoreactive with the memory B-cell receptors (33).…”
Section: Discussionmentioning
confidence: 99%
“…Once a diverse repertoire of T and B lymphocytes has been established, the development of antigenspecific immunity is a relatively straightforward Darwinian process (termed clonal selection) in which: 1) antigens bind to and activate specific lymphocytes with matching receptors, 2) selected lymphocytes undergo mitosis and pass on their genes to subsequent generations of daughter cells that share the same antigenic specificity, and 3) these lymphocytes orchestrate the process of antigen removal, and differentiate into long-lived memory cells (McClean et al, 1997;Paul, 1998;Roitt et al, 2001;Tonegawa, 1983). As with pathogens (or any organism, for that matter), population variation, heritability across generations, and differential reproductive success (the defining attributes of natural selection) are the primary forces that drive change in lymphocyte populations within an individual's lifetime.…”
Section: Development Of Human Immune Functionmentioning
confidence: 99%
“…The earliest such studies showed that developing B cells from xid mice could persist in the periphery but failed to do so when competing with wild-type B lineage progenitors [14]. More recent studies from the Freitas laboratory indicated that intraclonal competition, in terms of BCR specificity, determined relative competitive advantage among peripheral B cells [15,16]. Thus, comparisons of turnover rates in mixtures of BCR Tg and non-Tg cells revealed that a mature B cell's lifespan is not absolute, but instead depends on the clonotypic identities of co-existing competitors.…”
Section: B Cells Undergo Both Negative and Positive Selection As Theymentioning
confidence: 99%